Pengaruh Atribut Produlq Atribut Layanan, dan Atribut PembeHan terhadap Kepuasan Konsumen BEE'S F'amily Resto di Galeria MaIl Yoryakarta - Petra Surya Mega Wijaya; Debora S Suradal (Jurnal Riset Manajemen dan Bisnis, 2009)
Todcy, companies arc trying to do their best to satisfy crtstoners with their services and pro&rcts. They do vaious endcavors for the sa.ks of the astomer. Arnang these are improving tlrc qmlity of services, products, and axtomer relations. According to empirical research, there are three variables that shqe the customers' satisfactioA these are products attributes, services attributes and Trurchase attrib*es. Starting from the empirical .ftndW, this research ailned at uamining whether prodrct attributes, service attributes, and purchase attrihrtes influenced the anstomer satisfaction.  The research data was takcn from the anstomers of Bee's Family Resto at Galeria Mall, Yognkarta. One hundred customers were selected randomly to respond to some prepared qtestiotts in order to answer the research objectiws. This research wed Double Linear Regression to analyze the data collected.  The research result shmved that product attributes and purchase attributes hod a signifrcant inJluence on the c'nstometrs' satisfaction whereasthere was no significant influence between services attributes variable and cttstotners' I atisfaction.Keywords: Product Attributes, Sentices Attributes, Purchase Attributes,Customers' Satisfaction, Double Linear Regression, and Bee'sFamily Resto